Extramammary Paget's disease with ureteral metastasis: A case report - Shunsuke Nakamura; Naoya Murayama; Naoyoshi Satomi; Yoshiyuki Kamio; Yutaka Kuwatsuka; Yohei Shida; Junki Harada; Tomoaki Hakariya; Hideaki Sakai; Shinji Okano; Hiroyuki Murota (Wiley, 2024)
Abstract Extramammary Paget's disease (EMPD) is a skin cancer that can metastasize to distant lymph nodes and organs. However, there are no reports showing histological evidence of metastasis to the ureter. Here we report a case of EMPD that metastasized to the ureter in an 80‐year‐old man. The primary EMPD was resected and the right inguinal lymph node metastasis was dissected. Radiation therapy was administered around the right inguinal lymph nodes postoperatively. Four years later, a thickening of the wall of the right ureter was found, and a total right nephroureterectomy was performed due to suspicion of primary ureteral cancer. Histological examination showed nests of atypical cells in the renal adventitia and the surrounding lymphatic vessels, muscular layer and mucosal layer, but not in the ureteral epithelium. Immunohistochemical staining of tumour cells was positive for carcinoembryonic antigen, cytokeratin 7 and gross cystic disease fluid protein‐15 and was negative for cytokeratin 20. These results are consistent with a primary skin lesion. Although EMPD is not a frequent source of ureteral metastasis, EMPD can metastasize to the ureter. This case implies the feasibility of an accurate preoperative diagnosis through immunostaining, offering the potential to circumvent nephroureterectomy and instead facilitate appropriate management using a ureteral stent.